Analysis of Mathematical Concept Understanding Capabilities: The Impact of Makerspae STEM Learning Approach Models and Student Learning Activities - Komarudin Komarudin; Suherman Suherman; Anita Anggraini (Journal of Innovation in Educational and Cultural Research, 2021)
This research aims to determine the influence of students' learning activities on the ability to understanding mathematical concepts through the STEM Learning Approach Makerspace model based on PBL on SPLDV materials. As for the type of research Quasi-Experiments. The population in this study was 90 students who were distributed into 3 classes with 2 classes that sampled grades VIII A and VIII C. The sampling techniques in this study used randomized classes and data collection techniques in this study were tests and observations, while the research instruments used preliminary tests and final tests to measure the ability to understand mathematical concepts and observation sheets to see students' learning activities. Data analysis techniques using a two-way ANOVA test. The research showed that there is an influence of the PBL-based Makerspace STEM Learning Approach model on the ability to understand mathematical concepts, there is no influence on students' learning activities on mathematical concept comprehension capabilities, and there is no interaction between the PBL-based Stem Learning Approach Makerspace model and student learning activities on the ability to understand mathematical concepts. Conclusion, there is a positive direct effect of cognitive structures on the ability to understanding mathematical concepts.